2009
DOI: 10.1093/aob/mcp049
|View full text |Cite
|
Sign up to set email alerts
|

The ant-pollination system of Cytinus hypocistis (Cytinaceae), a Mediterranean root holoparasite

Abstract: Mutualistic services by ant are essential for the pollination of Cytinus hypocistis. Although this parasite does not exhibit typical features of the 'ant-pollination syndrome', many other characteristics indicate that it is evolving to a more specialized ant-pollination system. The striking interspecific differences in the pollination systems of Mediterranean Cytinus (ant-pollinated) and some South African Cytinus (mammal-pollinated) make this genus an excellent model to investigate the divergent evolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 69 publications
3
83
1
3
Order By: Relevance
“…The reproductive biology of the Cytinaceae is poorly known. Flowers of the European Cytinus hypocistus L. produce relatively limited nectar (ca 1 ml) and are visited by insects [17], as is the related genus Bdallophyton [18], whereas bird-pollination has been inferred for the South African Cytinus capensis Marloth, which has red flowers and produces abundant nectar [19].…”
Section: Methodsmentioning
confidence: 99%
“…The reproductive biology of the Cytinaceae is poorly known. Flowers of the European Cytinus hypocistus L. produce relatively limited nectar (ca 1 ml) and are visited by insects [17], as is the related genus Bdallophyton [18], whereas bird-pollination has been inferred for the South African Cytinus capensis Marloth, which has red flowers and produces abundant nectar [19].…”
Section: Methodsmentioning
confidence: 99%
“…Interactions vary from facultative to obligate and range from mutualism to parasitism. Plants benefit from ants via services including seed dispersal (Gallegos et al 2014), pollination (de Vega et al 2009), nutrient enrichment (Wagner and Fleur Nicklen 2010), and protection against herbivory (Trager et al 2010). In exchange, myrmecophilic plants provide food to ants, a process that is taxonomically widespread (Weber and Keeler 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study found that fire ants frequently foraged B. napus flowers, possibly producing negative effects on flower-visiting insects, including the Chinese honey bee Apis cerana F. (Hymenoptera: Apidae) and the cabbage white butterfly Pieris rapae (L.) (Lepidoptera: Pieridae). These flower-visiting insects usually play an important role in the reproduction of plants (Hickman 1974;Gómez et al 1996;Raju & Ezradanam 2002;de Vega et al 2009;Luo et al 2011Luo et al , 2012. Furthermore, fire ant workers foraged more frequently on plants when aphids were present, potentially leading to an increased problem for the pollinators.…”
Section: Introductionmentioning
confidence: 99%